DOES THE COVID-19 PANDEMI HAVE THE SAME IMPACT ON MANY INDUSTRIAL SECTOR? - Carolyn Lukita (Berkala Akuntansi dan Keuangan Indonesia, 2022)
The Covid-19 pandemic has resulted in a decline in purchasing power and the potential for economic recession in various countries, included public companies listed on the IDX which also experienced a decline in financial performance due to a decline in purchasing power. This study aims to analyze the impact of the Covid-19 pandemic on stock prices, financial performance, and financial risk. This study examines the differences in stock prices, financial performance, and financial risk between before and during the Covid-19 pandemic. The stock price used is the year-end closing stock price in 2019 and 2020. Meanwhile, financial performance is measured by profitability (ROA) and financial risk is measured by leverage (DER). This study suspects that there are significant differences in stock prices, financial performance, and financial risk during the Covid-19 pandemic that has emerged globally since early 2020. This study uses several sectors as research samples to analyze how the impact of Covid-19 in various sectors, includes: consumer goods, property and real estate and pharmaceutical sectors. This study uses a paired sample t-test, and the SPSS 23 application. The results of this study indicate that there are significant differences in the stock price, financial performance, and financial risk variables between before and during the occurrence of Covid-19 based on the overall data. Additional test results show that the property and real estate sectors are the sectors most affected by the consumer goods and pharmaceutical sectors. This research is expected to provide empirical evidence related to the impact of Covid-19 quantitatif so that later it can be used as information for investors in making decisions to buy, sell or hold shares during the Covid-19 pandemic.